2022
DOI: 10.3390/ijerph191912793
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Opinions towards Public Health Effects of Online Games: An Empirical Study Based on Social Media Comments in China

Abstract: Online game products have fueled the boom in China’s digital economy. Meanwhile, its public health concerns have sparked discussion among consumers on social media. However, past research has seldom studied the public health topics caused by online games from the perspective of consumer opinions. This paper attempts to identify consumers’ opinions on the health impact of online game products through non-structured text and large-size social media comments. Thus, we designed a natural language processing (NLP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Finally, Yin et al [39] explored Chinese attitudes toward volunteerism amid COVID-19 through social media comments to boost volunteer participation. Studies [40] have shown the impact of online games on public health through social media comments. Jeon et al [41] studied people's reactions to social media posts related to online games.…”
Section: Social Media Comments In Measuring Psychological Perceptionmentioning
confidence: 99%
“…Finally, Yin et al [39] explored Chinese attitudes toward volunteerism amid COVID-19 through social media comments to boost volunteer participation. Studies [40] have shown the impact of online games on public health through social media comments. Jeon et al [41] studied people's reactions to social media posts related to online games.…”
Section: Social Media Comments In Measuring Psychological Perceptionmentioning
confidence: 99%
“…Another important trend is the development of virtual reality and augmented reality technologies. With the continuous development of virtual reality and augmented reality technologies, the virtual reality gaming market will also usher in new opportunities [2]. Virtual reality games can provide a more immersive gaming experience, allowing users to interact more naturally with the gaming world.…”
Section: The Current Situation and Trends Of The Online Game Marketmentioning
confidence: 99%